Flow Distribution in Large Irrigation Channels in Zarafshon Basin - ugli, Nabiyev Dostonbek Zavkiy; Abdirashitovich, Khaydarov Safarboy; Abdukhamidovich, Meliyev Bakhtiyar; Rabimkulovich, Ganiyev Shahab; ugli, Amirkulov Mamatkul Davir (Miasto Przyszłości, 2024)
This article deals with using and distributing water in the Zarafshan River to large irrigation channels. The article provides information on the possibilities of effective use of the Dargom, Eski Ankhor and Narpai canals presented on the long-term water consumption observation.